Fetal Aortic Valvuloplasty for Evolving Hypoplastic Left Heart Syndrome: A Decision Analysis. Issue 4 (April 2020) - Pickard, Sarah S.; Wong, John B.; Bucholz, Emily M.; Newburger, Jane W.; Tworetzky, Wayne; Lafranchi, Terra; Benson, Carol B.; Wilkins-Haug, Louise E.; Porras, Diego; Callahan, Ryan; Friedman, Kevin G.
Abstract : Background: Fetal aortic valvuloplasty (FAV) may prevent progression of midgestation aortic stenosis to hypoplastic left heart syndrome. However, FAV has well-established risks, and its survival benefit remains unknown. Our primary aim was to determine whether FAV for midgestation aortic stenosis increases survival from fetal diagnosis to age 6 years. Methods and Results: We performed a retrospective analysis of 143 fetuses who underwent FAV from 2000 to 2017 and a secondary analysis of the Pediatric Heart Network Single Ventricle Reconstruction trial. Using these results, we developed a decision model to estimate probability of transplant-free survival from fetal diagnosis to age 6 years and postnatal restricted mean transplant-free survival time. FAV was technically successful in 84% of 143 fetuses with fetal demise in 8%. Biventricular circulation was achieved in 50% of 111 live-born infants with successful FAV but in only 16% of the 19 patients with unsuccessful FAV. The model projected overlapping probabilities of transplant-free survival to age 6 years at 75% (95% CI, 67%–82%) with FAV versus 72% (95% CI, 61%–82%) with expectant fetal management, resulting in a restricted mean transplant-free survival time benefit of 1.2 months. When limiting analyses to the improved FAV experience since 2009 to reflect current practice, (probability of technical success [94%], fetal demise [4%], and biventricular circulation [66%]), the model projected that FAV increased the probability of survival to age 6 years to 82% (95% CI, 73%–89%). Expectant management is favored if risk of fetal demise exceeded 12% or probability of biventricular circulation fell below 26%, but FAV remained favored over plausible recent range of technical success. Conclusions: Our model suggests that FAV provides a modest, medium-term survival benefit over expectant fetal management. Appropriate patient selection and low risk of fetal demise with FAV are critical factors for obtaining a survival benefit.